International food security politics - Amusan, Lere (Journal of the Belarusian State University. International Relations, 2021)
Food insecurity has been causing increasing concern since 2008 when food crises led to regime changes in the Maghreb and the Middle East. Some Arab states that survived the sweep of change have been trying to adjust their political systems along the line of Western democracy, albeit with a little degree of success. Although concern for food security led to the formation of some global organizations such as the United Nations’ Food and Agriculture Organization and the United Nations Children’s Fund, there is a greater need to focus on food insecurity that may emanate from the population explosion projected to hit 10 bln by 2050. Worth noting is a ruse of food security based on the use of alternatives to fossil fuel and animal feeds. This implies that despite an increase in grain production, the world is contending with unavailability, unaffordability, and inaccessibility to the quantity and quality of food, especially in developing nations. This is despite promises that largescale farming will neutralize food insecurity when it replaces subsistence farming, a system that focuses on agroecological food production rather than the recently imposed inorganic agriculture. In trying to capture the identified potential crisis, this paper relies on secondary sources of information and interrogates the problem through the employment of ecofeminism and agroecology paradigms with some elements of embedded liberalism. The paper concludes that organic farming is a sine qua non to food sovereignty in line with sustainable development goals.